Effectiveness of Ethnoscience Learning Based on Sasaknese Traditional Games: Preservice Teacher’s Perception - Agus Muliadi; M. Khairul Wazni; Suhirman Suhirman; Dadang Warta Chandra Wira Kusuma (Postgraduate, University of Mataram, 2024)
This study aims to explore the perceptions of preservice teachers on the effectiveness of ethnoscience learning based on Sasaknese traditional games. This exploratory research was conducted at the Mandalika University of Education with a subject pool of 294 preservice teacher students. The research utilized a validated closed questionnaire instrument with responses gathered using a Likert scale. The data from this study were analyzed using quantitative descriptive statistics. The results of this study are (1) preservice teachers’ perceptions of the effectiveness of ethnoscience learning based on Sasaknese traditional games in each item of the statement, namely item 1 scored 3.41, categorized as Very High; item 2 scored 3.19, categorized as Very High; item 3 scored 3.28, categorized as Very High; item 4 scored 3.13, categorized as Tall; item 5 scored 3.38, categorized as Very High; item 6 scored 3.37, categorized as Very High; and item 7 scored 3.47, categorized as Very High; (2) preservice teachers hold highly favorable perceptions regarding the effectiveness of ethnoscience learning based on Sasaknese traditional games have an average score of 3.32, categorized as Very High.